Effect of EDM parameters on material removal rate, tool wear rate and geometrical errors of aluminium material. (2021) - Selvarajan, L.; Sasikumar, R.; Senthil Kumar, N.; Kolochi, Prabu; Naveen Kumar, P.
Abstract: This investigation reveals the paradigm of EDM in this experiment to expel the metal from Al7075 with a performed Copper electrode. Aluminium7075 has the most elevated quality, higher firmness, and diminished thickness. Aluminium7075 is utilized prevalently in exceedingly focused on applications, for example, brackets, milk churns, mineral skips, cranes, external tank and scaffolds. Though EDM offers simple machinability joined with an excellent surface finish. Machine parameters of foremost noteworthiness, such as current (amp), pulse off time, pulse on time (µ sec), fluid pressure (kg/cm 2 ) and spark gap (mm) are contemplated utilizing Taguchi L18 orthogonal array. With the help of mean effective plots, tool wear rate (TWR), metal removal rate (MRR), cylindricity, circularity, and perpendicularity are examined. Information on such output levels and their impact on performance was investigated. The aftereffect of the investigation, the metal removal rate (MRR) increases when the current (10 amp) and pulse on time (29 µs) is increased. The tool wear rate (TWR) improves when the current (10 amp) and pulse on time (27 µs) is improved at the same time spark gap (0.4 mm) is reduced. And finally, the geometrical tolerance is also improved.